2003
DOI: 10.1152/ajpheart.00306.2003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of SM22α expression by arginine vasopressin and PDGF-BB in vascular smooth muscle cells

Abstract: This process involves coordinated changes in expression of multiple SM-specific genes. In cultured VSMC, arginine vasopressin (AVP) increases and PDGF decreases expression of SM ␣-actin (SMA), the earliest marker of SM cells (SMC). However, it is unknown whether these agents regulate other SM genes in a similar fashion. SM22␣ appears secondary to SMA during development and is also a marker for SMC. This study examined the regulation of SM22␣ expression by AVP and PDGF in cultured VSMC. Levels of SM22␣ mRNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Mutations in the CArG boxes of SM-specific genes inhibit expression of SM-markers during development, 5,6,14 and regulation by hormonal factors in cultured VSMC. 12,13,31,32 Phenotypic remodeling in mature vessels is regulated by local environmental cues including humoral factors, cell-cell and cell-matrix interactions, mechanical stresses, and inflammatory stimuli. Our laboratory has observed the convergence of signaling from both differentiating and dedifferentiating signals on SRF transactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the CArG boxes of SM-specific genes inhibit expression of SM-markers during development, 5,6,14 and regulation by hormonal factors in cultured VSMC. 12,13,31,32 Phenotypic remodeling in mature vessels is regulated by local environmental cues including humoral factors, cell-cell and cell-matrix interactions, mechanical stresses, and inflammatory stimuli. Our laboratory has observed the convergence of signaling from both differentiating and dedifferentiating signals on SRF transactivation.…”
Section: Discussionmentioning
confidence: 99%
“…AVP-induced increases in gene expression require c-jun amino terminal kinase and p38 MAP kinases, whereas PDGF-induced suppression is mediated by Ras, and phosphatidylinositol 3-kinase (PI3K)/Akt pathways. 1,[11][12][13] The promoters of these SM-genes contain common regulatory elements, specifically multiple CArG boxes, which have been shown to bind the MCM1, agamous, deficiens, serum response factor (MADS) box transcription factor, serum response factor (SRF). 14,15 Many SM-genes contain multiple CArG boxes in the proximal region of their promoter.…”
mentioning
confidence: 99%
“…Prolonged incubation of cells with TGF-␤ induces formation of stress fibres, inhibiting cell migration and invasion. Activation of the Ras-MEK-ERK-myc signalling pathway antagonises TGF-␤ inhibition of cell motility, and suppresses transgelin expression (Shields et al, 2002), as does immortalisation and transformation by RNA and DNA viruses (Kaplan-Alberquerque, Garat, Van Putten, & Nemenoff, 2003;Lawson et al, 1997). Expression of transgelin is decreased in breast and colon cancers (Shields et al, 2002;Wulfkuhle et al, 2002) and in prostate cancer (Yang et al, 2007;ourselves, unpublished data).…”
Section: Role In Pathologymentioning
confidence: 99%
“…It is known that local production of growth factors such as PDGF is involved in SMC phenotype switching, SMC migration, and vessel wall reorganization [11,12]. Previous studies indicated that PDGF-BB treatment significantly decreased production of SM-specific markers, such as SM α-actin, smooth muscle myosin heavy chain (SMMHC), and SM22α, in SMCs [10,24,29,30]. Our data showed that arsenic exposure-induced SMC alteration is accompanied by upregulation of Egr-1 and PDGF, suggesting that Egr-1/PDGF signaling is involved in early arsenic-mediated structural changes of the aorta.…”
Section: Discussionmentioning
confidence: 99%